Exegetical crossroads: understanding Scripture in Judaism, Christianity and Islam in the Pre-Modern Orient - Tamer, Georges; Grundmann, Regina; Kattan, Assaad Elias; Pinggéra, Karl (Judaism, Christianity, and Islam, 2018)
The art of interpreting Holy Scriptures flourished throughout the culturally heterogeneous pre-modern Orient among Jews, Christians and Muslims. Different ways of interpretation developed within each religion not without considering the others. How were the interactions and how productive were they for the further development of these traditions? Have there been blurred spaces of scholarly activity that transcended sectarian borders? What was the role played by mutual influences in profiling the own tradition against the others? These and other related questions are critically treated in the present volume.